Inactivation of phosphorylase phosphatase by a factor from rabbit liver and its chemical characterization as glutathione disulfide. - Takashi Shimazu; S. Tokutake; Makoto Usami (1978)
A factor inactivating phosphorylase phosphatase was isolated from rabbit liver. The isolation procedure consisted of heat treatment at 85 degrees C, extraction with n-butyl alcohol, and chromatography on Dowex 1 and DEAE-cellulose columns. The purified factor was different from the known protein inhibitors and was shown to be tripeptide composed of equimolar amounts of glutamic acid, cysteine, and glycine. The NH2-terminal and COOH-terminal amino acids were determined as glutamic acid and glycine, respectively. The factor was finally identified as glutathione disulfide by high voltage paper electrophoresis, paper chromatography, and liquid column chromatography using an amino acid analyzer. Addition of the purified factor or glutathione disulfide converted phosphorylase phosphatase to a stable, less active enzyme species, the extent of conversion depending on the amount added. The inactivated phosphatase was completely reactivated by addition of both glutathione (or 2-mercaptoethanol) and Mn2+ and partially reactivated by adding glutathione alone. Injection of glutathione disulfide into the portal vein of rabbits caused a rapid increase in phosphorylase alpha activity in the liver. These results suggest that glutathione disulfide is involved in regulation of phosphorylase activity in vivo, by causing inactivation of phosphorylase phosphatase in the liver.